2022
DOI: 10.1093/pm/pnac092
|View full text |Cite
|
Sign up to set email alerts
|

Dance for Chronic Pain Conditions: A Systematic Review

Abstract: Objectives Globally, 20–25% of people will experience chronic pain in their lifetime. Dance is a physical activity with psychosocial benefits which may positively impact pain. This review aimed to investigate the effect of dance interventions on the experience of pain, by quantitative measures and qualitative themes. Methods Seven major databases were searched from inception to January 2021. Two independent reviewers screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
1
3
0
1
Order By: Relevance
“…The outcomes of subgroup analysis also indicate that these differences had a limited impact on the overall results of the meta-analysis. Regarding the intervention duration, the findings of this review align closely with previous researches [45][46][47]. As a form of aerobic exercise, dance necessitates an intervention duration of at least 3 months to yield substantial effects on body composition.…”
Section: Discussionsupporting
confidence: 81%
“…The outcomes of subgroup analysis also indicate that these differences had a limited impact on the overall results of the meta-analysis. Regarding the intervention duration, the findings of this review align closely with previous researches [45][46][47]. As a form of aerobic exercise, dance necessitates an intervention duration of at least 3 months to yield substantial effects on body composition.…”
Section: Discussionsupporting
confidence: 81%
“…Nachgewiesen wurden positive Effekte bei Depressionen, schizophrenen Störungen, Autismus und somatoformen Störungen [4]. Ebenso wurden Verbesserun gen der Schmerzsymptomatik bei Patient*innen mit chronischen Schmerzen gezeigt [5].…”
Section: Das Konzept "Power Of Life Dance"unclassified
“…Chronic neck pain was reduced equally by direct neck motor control exercises and non-neck-specific muscle strengthening, possibly suggesting that attentional shifts can improve perceived symptoms, though improvement may also be related to the benefit of global reconditioning [77] . In a study of dance for chronic pain, many participants noted no decreased pain but rather improved acceptance of pain and improved mental and emotional well-being [78] . Similarly, studies using PT protocols for FND have not shown reduction in comorbid chronic pain, but did show improvements in social and physical function [79] , [80] .…”
Section: Physical Activity In Fnd and Comorbid Disordersmentioning
confidence: 99%